The Wedding at Cana (John 2:1-5): A Comparative Analysis of Religious, Scientific, and Cultural Perspectives - Belay Sitotaw Goshu Journal; Muhammad Ridwan; Arifulhak Aceh (Britain International for Academic Research (BIAR-Publisher), 2025)
Abstract: This study conducts a comparative analysis of John 2:1-5, the Wedding at Cana, across Ethiopian Orthodox, Catholic, Protestant, scientific, and cultural perspectives to explore theological, historical, psychological, and societal interpretations, fostering interfaith and interdisciplinary dialogue. Employing a qualitative comparative design, the study analyzes primary and secondary sources, including liturgical texts, theological commentaries, historical-critical studies, psychological frameworks, and cultural analyses. Findings reveal shared themes of divine power, obedience, and communal values. Ethiopian Orthodox theology emphasizes St. Mary’s intercessory role as the Theotokos, linking the miracle to Eucharistic symbolism and hospitality. Catholic interpretations highlight Mary’s mediation and the miracle’s sacramental significance, while Protestant exegesis prioritizes Christ’s divinity and obedience, minimizing Mary’s role. Historical-critical analysis situates the narrative in first-century Jewish wedding customs, with the water-to-wine transformation symbolizing the new covenant. Psychological perspectives interpret Mary’s and the servants’ actions as models of trust and prosocial behavior. Cultural analyses underscore hospitality, with Ethiopian contexts tying it to divine favor and Mediterranean settings to social honor. Differences emerge in Mary’s role, central in Ethiopian and Catholic traditions, secondary in Protestant, and in focus, with scientific and cultural lenses prioritizing historical and societal contexts. These findings bridge religious, scientific, and cultural interpretations, promoting dialogue and highlighting the passage’s enduring relevance in pluralistic societies.